THE CATALOGUE OF FRESHWATER DECAPODA (DECAPODA: POTAMONIDAE, ASTACIDAE, ATYIDAE) FROM THE REPUBLIC OF MACEDONIA IN THE COLLECTION OF MACEDONIAN MUSEUM OF NATURAL HISTORY - Valentina Slavevska-Stamenković, Biljana Rimčeska, Emilija Stojkoska, Nataša Stefanovska, Jelena Hinić, Vasil Kostov (Section of Natural, Mathematical and Biotechnical Sciences, MASA, 2016)
The catalogue summarizes the data found in the collection of freshwater decapods of the Macedonian Museum of Natural History in Skopje, Republic of Macedonia. In the present work we have also critically reviewed the historical data on the occurrence and distribution of representatives of decapods present in the country. The popula- tions of decapods have never been intensively studied in Macedonia, and thus, this catalogue may serve as a valuable source of data for nature conservation and protection of crustaceans and their habitats.
Keywords: catalogue; Decapoda; Macedonian Museum of Natural History; Macedonia